Pathological features of mammary analogue secretory carcinoma of the salivary gland - Shi, Ke (Int J Clin Exp Pathol, 2017)
The present study aimed to investigate the histopathological and immunohistochemical characteristics of Mammary Analogue Secretory Carcinoma (MASC) of the Salivary Gland. Methods: Four cases of MASC were diagnosed after microscope images review, immunohistochemsitry (IHC) for Mammaglobin protein, Gata3 protein, S-100 protein, DOG1 protein, and break-apart ETV6 fluorescence in situ hybridization (FISH) in forty salivary gland tumors. Results: We have shown a t(12;15)(p13;q25) ETV6-NTRK3 translocation in all but one case of MASC suitable for analysis. This translocation was not found in any other salivary gland tumor types including acinic cell carcinoma (AciCC, 30 cases) and mucoepidermoid carcinoma (MEC, 6 cases). In IHC, all MASC showed diffuse positivity for Mammaglobin protein, Gata3 protein and S100 protein, as the DOG1 was negative. Conclusions: MASC is rare tumor and often misdiagnosed as other salivary tumors, but whose specific histopathological, IHC and molecular genetic characteristics can help to identify it. ETV6-NTRK3 gene translocation is easily found in MASC, but may not occur in every case.